2018
DOI: 10.1111/dom.13541
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liraglutide on ambulatory blood pressure in patients with hypertension and type 2 diabetes: A randomized, double‐blind, placebo‐controlled trial

Abstract: Aims To assess the effect of liraglutide on 24‐hour ambulatory blood pressure and heart rate in patients with hypertension (pre‐ and stage 1 hypertension) and inadequately controlled Type 2 diabetes (glycated haemoglobin 7%–10% [53‐86 mmol/mol]). Materials and methods Eligible patients for this investigator‐initiated, parallel‐group, randomized, double‐blind trial were on stable background antihyperglycaemic therapy excluding insulin, glucagon‐like peptide‐1 receptor agonists and dipeptidyl‐peptidase‐4 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 31 publications
0
28
0
4
Order By: Relevance
“…A recent meta-analysis suggested that blood pressure lowering in early ischemic stroke had a neutral effect on the prevention of death or dependency [50]. Evidence for Cardiovascular Prevention from Observational Cohorts in Japan showed SBP was positively associated with ischemic stroke and intraparenchymal hemorrhage death [51].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis suggested that blood pressure lowering in early ischemic stroke had a neutral effect on the prevention of death or dependency [50]. Evidence for Cardiovascular Prevention from Observational Cohorts in Japan showed SBP was positively associated with ischemic stroke and intraparenchymal hemorrhage death [51].…”
Section: Discussionmentioning
confidence: 99%
“…These differences in blood pressure were much higher in our study than reported in LEAD studies that showed a reduction of systolic blood pressure between 2.7 and 2.9 mmHg [ 9 - 13 ]. Another randomized controlled trial analyzed the effect of liraglutide on blood pressure and compared it with placebo, showing a reduction in systolic blood pressure by -5.73 mmHg and a neutral effect on diastolic blood pressure by a mean difference of -1.42 mmHg [ 18 ]. Interestingly, a real-world evidence study from India showed a systolic blood pressure reduction of 9.7 mmHg, which was similar to that in our study [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Again, liraglutide caused a significant increase in the mean 24-hour heart rate by 6.16 beats/min. Of note, the beneficial effect of liraglutide on the 24-hour blood pressure was not associated with an increase in urine sodium excretion (44).…”
Section: Liraglutidementioning
confidence: 85%